Maize Water Productivity and Its Relationship to Soil Properties under Integrated Cattle Manure and Mineral‐Nitrogen Fertilizer in a Smallholder Cropping System. (1st November 2015) - Dunjana, Nothando; Nyamugafata, Philip; Nyamangara, Justice; Mango, Nelson; Gwenzi, Willis
Abstract : Crop water productivity is often regarded as indicating the water use efficiency of crops, an important aspect, particularly under erratic rainfall conditions. This study investigated the effects of cattle manure and mineral‐N fertilizer application on maize ( Zea mays L.) water productivity (MWP) on clay and sandy soils in a smallholder farming area of Zimbabwe. Four fields previously exhibiting heterogeneous fertility were managed under the following treatments: control (no amendment) and cattle manure (5, 15, and 25 Mg ha −1 ) + 100 kg ha −1 mineral‐N fertilizer for 7 yr. Thereafter, the effects of fertility treatment on MWP were expressed as actual maize grain yield produced per unit of seasonal transpiration modeled using AquaCrop. Furthermore, the relationship of MWP to physical soil properties was determined using principal component analysis. The MWP significantly ( P < 0.05) improved with an increase in cattle manure plus mineral‐N fertilizer application over control on both soils ranging between 0.5 and 1.7 kg m −3 and between 0.24 and 1.1 kg m −3 on clay and sandy soils, respectively. The MWP was significantly correlated ( P < 0.05) with the steady‐state infiltration rate on the clay soil and with soil organic C on the sandy soil. We concluded that cattle manure and mineral‐N fertilizer application is key to MWP improvement in rainfed smallholder cropping systems and is closely coupled with improvements in physical soil properties on clay soil than sandy soil. Therefore, the observations attest to the importance of site‐specific management that could contribute to efficient resource use in resource‐constrained farming areas.